2016
DOI: 10.1186/s12906-016-1201-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allodynic effect of intrathecal processed Aconitum jaluense is associated with the inhibition of microglial activation and P2X7 receptor expression in spinal cord

Abstract: BackgroundFor their analgesic and anti-arthritic effects, Aconitum species have been used in folk medicine in some East Asian countries. Although their analgesic effect is attributed to its action on voltage-dependent sodium channels, they also suppress purinergic receptor expression in dorsal root ganglion neurons in rats with neuropathic pain. In vitro study also demonstrated that the Aconitum suppresses ATP-induced P2X7 receptor (P2X7R)-mediated inflammatory responses in microglial cell lines. Herein, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…So, much research still needed to understand the homing capabilities of BMSCs. Intrathecal administration was used in this study for which had been proved a viable and effective option for gene therapy of chronic pain 24 , 25 in former studies.…”
Section: Discussionmentioning
confidence: 99%
“…So, much research still needed to understand the homing capabilities of BMSCs. Intrathecal administration was used in this study for which had been proved a viable and effective option for gene therapy of chronic pain 24 , 25 in former studies.…”
Section: Discussionmentioning
confidence: 99%
“…SNL-induced neuropathic pain is related to P2R activity [8]. In one study, the expression and production of spinal P2X7R increased following SNL surgery [34], while in another, the expression levels of P2X7R in the spinal cord segment were higher in the nerve surgery group than in the sham group [35,36]. Finally, P2X4 mRNA expression levels in the spinal horn increased following SNL surgery in mice [37].…”
Section: Discussionmentioning
confidence: 98%
“… 48 50 Previous research has suggested the presence of P2X 7 receptor in the dorsal root ganglion and spinal cord dorsal horn and its involvement in neuropathic pain mechanism in rats. 51 , 52 The studies suggested that P2X 7 receptors are involved in the modulation of neuropathic pain in relation to the following factors. (1) Purine signaling can be conducted by non-synaptic routes.…”
Section: Discussionmentioning
confidence: 99%